Between the Cracks of History - Satterwhite, Carolyn Fiedler; Abernethy, Francis Edward; Project Muse. (University of North Texas Press, 1997)
Annotation Six essays discuss definitions and explanations of folklore, and methods of teaching it. Then 15 additional essays explore Texas folklore related to such topics as police burials, gang graffiti, fiddling, ghosts, dance halls, oil fields, spring rituals, and the dialect spoken along the border between Texas and Mexico. Numerous illustrations and black-and-white photographs. Annotation copyrighted by Book News, Inc., Portland, OR.
Between the cracks of history -- Classroom definitions of folklore / F.E. Abernethy -- Defining folklore for my students / Joyce Roach -- Folklore and cinema / Jim Harris -- Toward a definition of folk culture / Joe S. Graham -- Folklore fieldwork on the Internet : some ethical and practical considerations / Jan Roush -- Beginning within : teaching folklore the easy way / Rhett Rushing -- The honored dead : the ritual of police burial / Phyllis Bridges -- Meaner than Hell! / Kenneth W. Davis -- Gang graffiti / Ken Untiedt -- Gideon Lincecum, "Killie Krankie," and fiddling in early Texas / Chris Goertzen -- The bluebird mare from Sterling City / Patrick Dearen -- The night the stars fell / Robert J. Duncan -- Rail tales : some are true / Charlie Oden -- Dance halls of East Texas : from oral history / Dennis Read and Bobby Nieman -- The oil field camp / James Winfrey -- Noises in the attic : adventures of some Texas ghosts / Allan Turner and Richard Stewart -- Repo man / John Lightfoot -- Tex-Mex dialect, or, Gidget goes to Acuna / Rebecca Cornell -- Punching sticks, flannel wrapped bricks, and pink powder purgatives : spring rituals / Ernestine Sewell Linck -- When Harley Sadler's tent show came to town / J.G. Pinkerton -- Eating over the sink and other marital strategies / James Ward Lee.
Description based on print version record.
Keywords: Folklore -- Study and teaching; Folklore; Folklore -- Étude et enseignement; Folklore; Folklore -- Texas; Folklore. -- Study and teaching; Folklore; Folklore -- Texas; Folklore -- Study and teaching; Folklore; Folklore -- Texas; Texas; Folk literature; Folklore; Folk literature; Electronic books